The awareness of the extensible business reporting language (XBRL) in Malaysia - Ilias A.; Abd Razak M.Z.; Abd Razak S.F.F. (ARRAY Development (Canada) Inc., 2023)
The current study had explored the Extensible Business Reporting Language (XBRL) among various stakeholders from a financial reporting perspective. In addition, the impact of the benefits on users, organization and preparers might vary according to the culture, country or financial regulations. Thus, this research will focus on Malaysia since Malaysia is multi-cultural and the adoption of XBRL can be considered as a new development. Pertaining to this research, it is important to understand the concept of a new reporting technology and the way XBRL will provide interactive data. The awareness and intention to adopt the XBRL will resume effectively once users, preparers and regulators are able to understand the whole concept of XBRL. This research is considered significant in order to explore the readiness and awareness of new reporting technology in Asia, particularly in Malaysia. This study found only a few respondents was fully aware of XBRL, while the majority of respondents were unaware about XBRL. Besides awareness, the study found that there are approximately 67.2% of respondents who are likely to investigate the XBRL technology, which indicates that there is a possibility that XBRL will be more significant and eventually accepted by stakeholders. This study found that approximately 3.1% understood fully what XBRL is and 18% understood the basic concepts. © Azleen Ilias, Mohd Zulkeflee Abd Razak and Siti Fara Fadila Abd Razak, 2014.